αν f'(x)=f(x) τότε f(x)=e^{x}

Απόδειξη.

Δίνεται f'(x)=f(x) (1)

Θεωρώ τη συνάρτηση g(x)=f(x)e^{-x}.

H e^{-x} είναι παραγωγίσιμη ως σύνθεση των παραγωγίσιμων -x και e^{x}.

H g ως γινόμενο των παραγωγίσιμων συναρτήσεων f και e^{-x} θα είναι παραγωγίσιμη με

g'(x)=f'(x)e^{-x}+f(x)[-e^{-x}]=f(x)e^{-x}-f(x)e^{-x}   [λόγω της σχέσης (1)]

=0.

Άρα η g είναι σταθερή συνάρτηση. Δηλαδή υπάρχει πραγματικός αριθμός c τέτοιος ώστε

g(x)=c, δηλαδή f(x)e^{-x}=c, δηλαδή f(x)=ce^{x}.

Advertisements
This entry was posted in exercises. Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s